Epigenetic modifier Kdm6a/Utx controls the specification of hypothalamic neuronal subtypes in a sex-dependent manner - Cabrera Zapata, Lucas E.; Cambiasso, María Julia; Arevalo, Maria Angeles (Frontiers in Cell and Developmental Biology, 2022)
Kdm6a is an X chromosome-linked H3K27me2/3 demethylase that promotes chromatin accessibility and gene transcription and is critical for tissue/cell-specific differentiation. Previous results showed higher Kdm6a levels in XX than in XY hypothalamic neurons and a female-specific requirement for Kdm6a in mediating increased axogenesis before brain masculinization. Here we explored the sex-specific role of Kdm6a in the specification of neuronal subtypes in the developing hypothalamus. Hypothalamic neuronal cultures were established from sex-segregated E14 mouse embryos and transfected with siRNAs to knockdown Kdm6a expression (Kdm6a-KD). We evaluated by immunofluorescence the effect of Kdm6a-KD on Ngn3, a bHLH transcription factor regulating neuronal sub-specification in hypothalamus. Kdm6a-KD decreased Ngn3 expression in females but not in males, abolishing basal sex differences. Then, we analyzed Kdm6a-KD effect on Ascl1, Pomc, Npy, Sf1, Gad1 and Th expression by RT-qPCR. While Kdm6a-KD downregulated Ascl1 in both sexes equally, we found sex-specific results for Pomc, Npy and Th. Pomc and Th expressed higher in female than in male neurons and Kdm6a-KD reduced their levels only in females, while Npy expressed higher in male than in female neurons and Kdm6a-KD upregulated its expression only in females. Identical results were found by immunofluorescence for Pomc and Npy neuropeptides. Finally, using ChIP-qPCR we found higher H3K27me3 levels at Ngn3, Pomc and Npy promoters in male neurons, in line with Kdm6a higher expression and demethylase activity in females. These results indicate that Kdm6a plays a key sex-specific role in controlling the differentiation of neuronal populations regulating food intake and energy homeostasis.